A common pattern of brain MRI imaging in mitochondrial diseases with complex I deficiency. Issue 1 (23rd October 2010) - Lebre, A S; Rio, M; Faivre d'Arcier, L; Vernerey, D; Landrieu, P; Slama, A; Jardel, C; Laforêt, P; Rodriguez, D; Dorison, N; Galanaud, D; Chabrol, B; et al.
Abstract : Objective: To identify a consistent pattern of brain MRI imaging in primary complex I deficiency. Complex I deficiency, a major cause of respiratory chain dysfunction, accounts for various clinical presentations, including Leigh syndrome. Human complex I comprises seven core subunits encoded by mitochondrial DNA (mtDNA) and 38 core subunits encoded by nuclear DNA (nDNA). Moreover, its assembly requires six known and many unknown assembly factors. To date, no correlation between genotypes and brain MRI phenotypes has been found in complex I deficiencies. Design and subjects: The brain MRIs of 30 patients carrying known mutation(s) in genes involved in complex I were retrospectively collected and compared with the brain MRIs of 11 patients carrying known mutations in genes involved in the pyruvate dehydrogenase (PDH) complex as well as 10 patients with MT-TL1 mutations. Results: All complex I deficient patients showed bilateral brainstem lesions (30/30) and 77% (23/30) showed anomalies of the putamen. Supratentorial stroke-like lesions were only observed in complex I deficient patients carrying mtDNA mutations (8/19) and necrotising leucoencephalopathy in patients with nDNA mutations (4/5). Conversely, the isolated stroke-like images observed in patients with MT-TL1 mutations, or the corpus callosum malformations observed in PDH deficient patients, were never observed in complex I deficient patients. Conclusion: A common pattern of brain MRI imaging was identified with abnormal signal intensities in brainstem and subtentorial nuclei with lactate peak as a clue of complex I deficiency. Combining clinico-biochemical data with brain imaging may therefore help orient genetic studies in complex I deficiency.